Optimizing the addition of flocculants for recycling mineral-processing wastewater. Issue 2 (3rd March 2016) - Park, Jin Hee; Oh, Chamteut; Han, Young-Soo; Ji, Sang-Woo
Abstract: Mineral processing requires large volumes of water, but water is limited at mining sites. Therefore, techniques to recycle mineral-processing wastewater without negative effects on recovery and flotation grade are critical. Among a number of technologies to recycle water, flocculation using an anionic polymer was tested for recycling mineral-processing wastewater, as a major issue in mineral-processing wastewater recycling is to reduce suspended particles. A batch cylinder test was employed to evaluate the optimum amount of flocculant to add and settlement rate, turbidity, and floc size were measured as indications of dewaterability. Adding increasing amounts of flocculant increased the sedimentation rate due to the increased floc size. However, turbidity did not improve by increasing the concentration of flocculant because the polymer coating on the particle surface prevented efficient bridging of particles. In addition, excess use of flocculant may degrade water quality and produce unnecessary costs. Therefore, it is important to identify the optimum flocculant concentration for treating mineral-processing wastewater based on the properties of the water.